DA-9805, a Herbal Mixture, Restores Motor Manifestations in 6-Hydroxydopamine-induced Parkinson’s Disease Mouse Model by Regulating Striatal Dopamine and Acetylcholine Levels - Huh, Eugene; Kwon, Youngji; Choi, Jin Gyu; Lim, Myung Gyu; Jeong, Jin Seok; Park, Ah Yeon; Kim, Jeong Hee; Pak, Youngmi Kim; Hong, Seon-Pyo; Oh, Myung Sook (Frontiers in Pharmacology, 2022)
Loss of dopamine (DA) is one of the primary features of Parkinson’s disease (PD); however, imbalances of non-dopaminergic neurotransmitters significantly contribute to the disabilities noted in advanced PD patients. DA-9805 is the ethanolic extraction of the root bark of Paeonia × suffruticosa Andrews [Paeoniaceae], the root of Angelica dahurica (Hoffm.) Benth. & Hook.f. ex Franch. & Sav. [Apiaceae] and the root of Bupleurum falcatum L. [Apiaceae], which have been widely utilized as an enhancer of motor function in East Asia. This study aimed to investigate whether DA-9805 modified motor dysfunctions and imbalances associated with DA and other neurotransmitters in a 6-hydroxydopamine-induced PD mouse. We confirmed the expressions of proteins related with neurotransmissions in the striatum. In addition, we measured the striatal neurotransmitters using HPLC and analyzed their correlation. DA-9805 significantly improved motor impairments and restored the altered levels of neurotransmitters in the striatum. Moreover, DA-9805 improved the altered expressions of tyrosine hydroxylase (TH), DA transporter, and choline acetyltransferase (ChAT) in the ipsilateral part of mouse striatum or SNpc, which implies the neuroprotection. We also found that the level of striatal acetylcholine (Ach) has the moderate negative correlation with motor functions and TH expression in the SNpc. This study indicates that DA-9805 restores motor dysfunctions by normalizing the increased levels of striatal Ach via modulating DA transmission and ChAT expressions as well as its neuroprotective effects.